Principles of operations management sustainability and supply chain management - Heizer, Jay H. 1935-; Render, Barry 1946-; Munson, Chuck (Pearson, 2021)
This title is a Pearson Global Edition. The Editorial team at Pearson has worked closely with educators around the world to include content, which is especially relevant to students outside the United States. For courses in operations management. A broad introduction to oper